KONSEP PENDIDIKAN ISLAM PERSPEKTIF H.O.S TJOKROAMINOTO - Arif Rahman Hakim; Wirano Wirano (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
The values ??of Islamic teachings brought by the great prophet Muhammad SAW, according to him, if we further explore and learn about them in Islam they will be implemented in life and nationality, and can also help face all the problems faced by the Indonesian people . In essence, the main idea of ??Islamic socialism according to the understanding of HOS Tjokrominoto is how to position and function religion (in this case Islam) as a revolutionary force to liberate oppressed people both culturally and politically and politically. HOS Tjokroaminoto is the son of a priyai who started the struggle against colonialism through the Sarekat organization Islam which is based on Islamic ideology and Socialism. HOS Tjokroaminoto's Islamic education perspective is very significant in a country. Education in question is education based on Islamic teachings, because in that teaching humans can find national values.